Finite element analysis on hot deformation behavior of TiC-particle-reinforced titanium matrix composite. Issue 6 (29th July 2014) - Song, Weidong; Tang, H.P.; Mao, X.N.
Abstract : Purpose: – The purpose of this paper is to investigate tensile properties of TiC particle-reinforced titanium matrix composites (PRTMC) using the elasto-plastic finite element (FE) programs and the homogenization method and the fixed point iteration method. Design/methodology/approach: – Two quasi-static and dynamic transient programs of elasto-plastic FE were coded by using FORTRAN. Based on the FE programs, the FE model of the TiC PRTMC with typical microstructures was established by using the fixed point iteration method and the homogenization theory. The hot deformation behavior of TiC PRTMC under different temperatures were analyzed by using the above model and programs. Findings: – Calculation results are presented to investigate the influence of different temperatures on the hot deformation behavior of TiC PRTMC. Based on the experimental data, a good agreement was obtained between the numerical predictions and the experimental results, and the feasibility of this method was verified. Originality/value: – The work is original and findings are new, which demonstrates this FE frame combined with the homogenization method and the fixed point iteration method can be used to investigate the tensile behavior of particle-reinforced metal matrix composites.